Perlindungan Sosial Inklusif Bagi Lanjut Usia (Lansia) di Kelurahan Mangalli Kecamatan Pallangga Kabupaten Gowa - Jannah, Miftahul; Idrus, Idham Irwansyah; Tamrin, Sopian (Prodi Sosiologi FISIP Universitas Teuku Umar, 2024)
This research seeks to ascertain: 1) the execution of inclusive protection for the elderly in Manggali Village, Pallangga Sub District, Gowa District; and 2) the obstacles to comprehensive social protection for the elderly in Manggali Village, Pallangga Sub District, Gowa District. This study is qualitative and utilizes a descriptive methodology, and also employs a purposive sample method to identify informants, comprising the elderly, government personnel from Mangalli Village, community members, and older cadres. The data collection methods were observation, interviews, and documentation. The study confirms the validity of the data via source triangulation and utilizes data reduction, data presentation, and conclusion formulation as techniques of analysis. The research findings indicate that firstly, Government initiatives, including administrative services, social assistance, social services, and social security, offer comprehensive social protection for the elderly in Mangalli Village, Pallangga District, Gowa Regency. Secondly, The obstacles to inclusive social protection in Mangalli Village, Pallangga Sub District, Gowa District encompassing the health status of the elderly, the incomplete documentation of elderly individuals lacking identity cards (KTPs) and family cards, the absence of annual updates to government data, and insufficient budget allocation.